A Knittable Fibriform Supercapacitor Based on Natural Cotton Thread Coated with Graphene and Carbon Nanoparticles. (10th July 2016) - Ye, Xingke; Zhou, Qianlong; Jia, Chunyang; Tang, Zhonghua; Wan, Zhongquan; Wu, Xiaochun
Graphical abstract: Highlights: The rGO-CT was fabricated via dip-coating and vapour reduction method. The rGO nanosheets wrapped CT has impressive conductivity. The rGO nanosheets with implanted CNPs form the 3D hierarchical nanostructures. The two kinds of FSCs have long cycle life and excellent electrochemical stability. The FSC based on CNPs/rGO-CT can be knitted into textile while maintaining its initial performance. Abstract: Fibriform supercapacitors (FSC) are promising energy storage devices for wearable electronics which require excellent durability and fabric-like wearable comfort. In this work, we successfully converted commercial cotton threads (CT) into electrically conductive and electrochemically active threads by introducing reduced graphene oxide (rGO) and carbon nanoparticles (CNPs) using a large-scale producible method (dip-coating combined with low-temperature vapour reduction). The rGO coated CT (rGO-CT) has impressive conductivity which is attributed to the wrapped rGO nanosheets and it is steady enough to tolerate washing process for a long time. After coated with CNPs, the conductivity of CNPs/rGO composites coated CT (CNPs/rGO-CT) has been enhanced tremendously. Meanwhile, the rGO nanosheets with implanted CNPs form the three-dimensional (3D) hierarchical nanostructures which provide abundant ion transmission channels. Furthermore, we have prepared the CNPs/rGO-CT based FSC, which exhibits high volumetric capacitance (3.79 mF cm −3 at 50 mV s −1 ), well cycling stability (95.23% capacitance retention after 10000 charge-discharge cycles), and excellent electrochemical stability (92.30% capacitance retention after 2000 bending cycles). Especially, the CNPs/rGO-CT based FSC maintains great capacitive performance when it was knitted into textile, thus making it meet the high performance requirements of energy storage devices for knittable and wearable electronics.